Pioglitazone together with imatinib in chronic myeloid leukemia: A proof of concept study. Issue 10 (27th December 2016) - Rousselot, Philippe; Prost, Stéphane; Guilhot, Joelle; Roy, Lydia; Etienne, Gabriel; Legros, Laurence; Charbonnier, Aude; Coiteux, Valérie; Cony‐Makhoul, Pascale; Huguet, Francoise; Cayssials, Emilie; Cayuela, Jean‐Michel; et al.
Abstract : BACKGROUND: We recently reported that peroxisome proliferator‐activated receptor γ agonists target chronic myeloid leukemia (CML) quiescent stem cells in vitro by decreasing transcription of STAT5 . Here in the ACTIM phase 2 clinical trial, we asked whether pioglitazone add‐on therapy to imatinib would impact CML residual disease, as assessed by BCR‐ABL1 transcript quantification. METHODS: CML patients were eligible if treated with imatinib for at least 2 years at a stable daily dose, having yielded major molecular response (MMR) but not having achieved molecular response 4.5 (MR 4.5 ) defined by BCR‐ABL1/ABL1 IS RNA levels ≤ 0.0032%. After inclusion, patients started pioglitazone at a dosage of 30 to 45 mg/day in addition to imatinib. The primary objective was to evaluate the cumulative incidence of patients having progressed from MMR to MR 4.5 over 12 months. RESULTS: Twenty‐four patients were included (age range, 24‐79 years). No pharmacological interaction was observed between the drugs. The main adverse events were weight gain in 12 patients and a mean decrease of 0.4 g/dL in hemoglobin concentration. The cumulative incidence of MR 4.5 was 56% (95% confidence interval, 37%‐76%) by 12 months, despite a wide range of therapy duration (1.9‐15.5 months), and 88% of 17 evaluable patients who were still on imatinib reached MR 4.5 by 48 months. The cumulative incidence of MMR to MR 4.5 spontaneous conversions over 12 months was estimated to be 23% with imatinib alone in a parallel cohort of patients. CONCLUSION: Pioglitazone in combination with imatinib was well tolerated and yielded a favorable 56% rate. These results provide a proof of concept needing confirmation within a randomized clinical trial (EudraCT 2009‐011675‐79). Cancer 2017;123:1791–1799 . © 2016 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. Abstract : Pioglitazone is a peroxisome proliferator‐activated receptor gamma agonist that is able to target quiescent chronic myeloid leukemia stem cells. The combination of imatinib and pioglitazone was well tolerated in vivo and induced a cumulative incidence of conversion to molecular response 4.5 (MR4.5) of 56% by 12 months in 24 CML patients who had a major molecular response under imatinib alone.